Mission ImPOxable – or the unknown utilization of non-toxic poly(2-oxazoline)s as cryoprotectants and surfactants at the same time. Issue 46 (15th November 2017) - Leiske, Meike N.; Trützschler, Anne-Kristin; Armoneit, Sabine; Sungur, Pelin; Hoeppener, Stephanie; Lehmann, Marc; Traeger, Anja; Schubert, Ulrich S.
Abstract : Polymeric nanoparticles are produced using hydrophilic poly(2-oxazoline)s (P(Ox)s) as particle stabilizers during preparation, purification and lyophilization as an all-in-one system. Abstract : Polymer based nanoparticles offer great opportunities for diverse applications, i.e. their drug delivery potential is promising. However, their major drawback is identified in preparation via the nanoemulsion technique, which is needed for the encapsulation of hydrophilic drugs and whereby the utilization of surfactants, e.g. poly(vinyl alcohol) (PVA), is mandatory. Furthermore, the preparation of nanoparticles is critical due to the need of lyophilization for storage. For this reason it is common to use cryoprotectants, which are usually sugar based. In the current study, we present the use of non-toxic, water-soluble poly(2-oxazoline)s (P(Ox)s) in terms of polymeric nanoparticle stabilizers for preparation, purification, and lyophilization. The nanoparticles were characterized via dynamic light scattering (DLS) and cryo-transmission electron microscopy (cryoTEM). The use of hydrophilic P(Ox)s with a degree of polymerization of about 60 yielded stable nanoparticles. For the preparation via nanoemulsion a PDI below 0.2 could be obtained after adjustment of the surfactant concentration. All nanoparticles were in the size range of 100 to 200 nm according to DLS. Furthermore, the addition of P(Ox) was beneficial during particle purification via centrifugation and filtration as well as lyophilization, yielding nanoparticles with a PDI below 0.3 as determined via DLS and confirmed via cryoTEM measurements. Cytotoxicity, hemolysis and erythrocyte aggregation measurements of these P(Ox)s did not show any harmful effect on the treated cells.